Analysis of Operative Mortality and Post-operative Lethal Complications after Head and Neck Reconstruction with Free Tissue Transfer - Tanaka, K.; Sakuraba, M.; Miyamoto, S.; Hayashi, R.; Ebihara, M.; Miyazaki, M.; Shinozaki, T.; Daiko, H.; Yano, T. (Japanese journal of clinical oncology, 2011)
Operative mortality is the most important index for assessing operative results, which has rarely been examined in reconstructive surgery. The aims of this study were to establish a representative index of operative mortality after head and neck reconstruction and to consider measures to improve operative results. We reviewed cases of head and neck reconstruction by means of free tissue transfer performed from July 1992 through December 2005 at the National Cancer Center Hospital East, Chiba, Japan. The subjects were 1249 patients with a mean age of 62 years. Operative mortality was evaluated on the basis of the 30-day post-operative mortality rate and the in-hospital mortality rate. Statistical analysis was performed with the Cochran-Armitage test. The 30-day post-operative mortality rate was 0.88% (11 of 1249 patients), and the in-hospital mortality rate was 1.84% (23 of 1249 patients). The 30-day post-operative mortality was significantly correlated with age (P = 0.002), but the in-hospital mortality was not (P = 0.148). Among patients older than 80 years, the 30-day post-operative mortality rate was 8.57%. The most common cause of 30-day post-operative death was cerebral infarction. Of the 23 in-hospital deaths, 13 were due to cancer recurrence. These results indicate that head and neck reconstruction with free flaps is reliable. However, the high 30-day post-operative mortality rate among patients 80 years or older should be considered when deciding whether to operate. To decrease the operative mortality rate, careful perioperative management is needed to prevent complications and shorten the hospital stay.